TLR4 promotes fibrosis but attenuates tubular damage in progressive renal injury - Pulskens, Wilco P; Rampanelli, Elena; Teske, Gwendoline J; Butter, Loes M; Claessen, Nike; Luirink, Ilse K; van der Poll, Tom; Florquin, Sandrine; Leemans, Jaklien C (Journal of the American Society of Nephrology, 2010)
Toll-like receptors (TLRs) can orchestrate an inflammatory response upon activation by pathogen-associated motifs and release of endogenous stress ligands during tissue injury. The kidney constitutively expresses most TLRs, including TLR4. The function of TLR4 during the inflammation, tubular atrophy, and fibrosis that accompany progressive renal injury is unknown. Here, we subjected wild-type (WT) and TLR4-deficient mice to unilateral ureteral obstruction and observed elevated levels of TLR4 mRNA in the kidney after obstruction. One day after unilateral ureteral obstruction, TLR4-deficient mice had fewer proliferating tubular epithelial cells and more tubular damage than WT mice; however, TLR4-deficient mice developed considerably less renal fibrosis despite decreased matrix metalloproteinase activity and without significant differences in myofibroblast accumulation. In vitro, TLR4-deficient primary tubular epithelial cells and myofibroblasts produced significantly less type I collagen mRNA after TGF-beta stimulation than WT cells. The reduced fibrosis in TLR4-deficient mice associated with an upregulation of Bambi, a negative regulator of TGF-beta signaling. In conclusion, TLR4 attenuates tubular damage but promotes renal fibrosis by modulating the susceptibility of renal cells to TGF-beta. These data suggest that TLR4 signaling may be a therapeutic target for the prevention of renal fibrosis.